Cardiovascular damage in seronegative spondylarthritis - STOICA, Mihaela; SCORPAN, Anatolie; SARBU, Oxana; GOREA, Alexandru; ISTRATI, Valeriu (One Health & Risk Management, 2022)
Introduction. Cardiovascular mortality in patients diagnosed with seronegative spondyloarthritis (SSN) is on the rise. Impairment of the cardiovascular system in ankylosing spondylitis (SpA) is 20-40%, in psoriatic arthritis (APs) 18-22% and in reactive arthritis (ARe) 1-3%. Material and methods. The study included 77 patients diagnosed with SSN. Laboratory (erythrocyte sedimentation rate – ESR, C-reactive protein – CRP, fibrinogen) and instrumental (echocardiography – EcoCG, electrocardiogram – ECG) data were analyzed. Results. In 35 patients diagnosed with SpA, the left branch hemiblock of the Hiss bundle was determined – 71% and bradycardia – 57%. Aortic valve (VAo) changes were diagnosed in 54% and left ventricular hypertrophy (LVH) in 57%. Elevated CRP values were found in 34.5% of cases, ESR – 22.8% and fibrinogen – 17.2%. In 24 patients with APs, 33.5% showed VAo induration and fibrosis. Another change diagnosed in these patients was LVH (37.5%). Cardiac conductivity disorders in 25% were due to the left branch hemiblock of the Hiss bundle, and among the increased inflammatory markers were: fibrinogen (16.6%) and CRP (12.5%). In 18 patients with ARe as a rhythm disorder, tachycardia is predominant – 94% and VAo damage in 27.7%. Inflammatory markers with values above the upper limit were fibrinogen (66%) and CRP (33%). Conclusions. Our study showed that SSN is closely related to the inflammatory syn-drome, on which the activity of the disease and the degree of damage to the cardiovascular system depend. Most often the heart is affected with its components.